Characterization And Properties Of Ultrafine Silica As A Filler In Natural Rubber Compounds - Idrus, Siti Suhaida (2011)
In Malaysia, silica had been selling in crude way and part of it was being exported to overseas to be value added and yet Malaysia is importing the high quality silica for the local manufacturing industry consumption. Besides agglomeration problem, this imported precipitated silica was very expensive. Therefore, upgrading local silica in term of physical and chemical characteristics could be the best solution. In this study, there are two major parts involved, i.e. value adding of silica to become ultrafine silica via air classification and incorporation of ultrafine silica as a filler in SMR L grade natural rubber.